2020
DOI: 10.3390/su12166380
|View full text |Cite
|
Sign up to set email alerts
|

Scenario-Based Allocation of Emergency Resources in Metro Emergencies: A Model Development and a Case Study of Nanjing Metro

Abstract: As metro systems are becoming more and more widely used, all kinds of emergencies happen from time to time. A series of cases indicate that inefficient emergency response is a dominating cause of tremendous casualties and losses. The fast and valid allocation of emergency resources after the occurrence of metro emergencies has become a key point in improving the sustainability of metro operations. However, few studies have attempted to determine the allocation of emergency resources in metro emergencies. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Most of the current research on emergency management has focused on management structures [ 74 ], management methods [ 75 ], software systems [ 76 ], and conceptual theories [ 77 ]. There is less research on the role of disaster prevention facilities in the emergency management process.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the current research on emergency management has focused on management structures [ 74 ], management methods [ 75 ], software systems [ 76 ], and conceptual theories [ 77 ]. There is less research on the role of disaster prevention facilities in the emergency management process.…”
Section: Discussionmentioning
confidence: 99%
“…Garrido and Aguirre (2017) proposed a mixed-integer model, which was a stochastic one, that reduced response time during the assistance of victims of the earthquake. Lu and Sun (2020) developed a multiobjective model that minimized penalty cost and the sum of allocation cost for allocating emergency resources in the rescue process of metro emergency, and they used a scenario-based analysis. Su et al (2016) proposed a constrained integer linear programming model and identified overlapping disaster response coalitions for concurrent incidents.…”
Section: Facility Location Problem Focusing Emergency Responsementioning
confidence: 99%
“…Distance is commonly measured by Euclidean distance and Manhattan distance [24][25][26]. For emergency travel time, most studies have been derived from Global Information System or estimated from scenario settings [27][28][29][30]. However, little research has been done on the problems arising from the performance of dynamic road networks, and there is a research gap of combining resource allocation with path planning.…”
Section: Introductionmentioning
confidence: 99%